Association between asthma and body mass index and socioeconomic status: A cross‐sectional study on 849 659 adolescents. Issue 1 (22nd September 2015) - Gordon, Barak; Hassid, Aviad; Bar‐Shai, Amir; Derazne, Estela; Tzur, Dorit; Hershkovich, Oded; Afek, Arnon
Abstract: Background and objective: Asthma is associated with body mass index (BMI), but its association with socioeconomic status (SES) is controversial. The combined effect of SES and BMI on asthma prevalence is undetermined. Methods: Seventeen‐year‐old pre‐recruits to the Israeli Defense Forces underwent routine physical examinations. SES was determined according to established criteria based on place of residence. The study population was divided according to classic weight groups and three SES groups (low, medium and high). Univariable and multivariable logistic regression models were applied to assess odds ratios (OR) of BMI and SES groups for asthma prevalence. The combined effect of BMI and SES was also calculated. Results: The 849 659 subjects included 480 993 males (9.5% asthma prevalence) and 368 666 females (6.7% asthma prevalence). Increased BMI were associated with increased OR for asthma in females (1.44, 95% CI 1.36–1.52 for obese vs normal weight). Males had a J‐shaped curve (OR 1.24 95% CI 1.2–1.29 for obese, 1.12, 95% CI 1.08–1.16 for underweight, both vs normal weight). OR adjusted to SES did not change significantly. All SES groups produced a linear curve (1.59 95% CI 1.53–1.66 for females and 1.79 95% CI 1.74–1.84 for males). Adjustment of SES to BMI produced no significant change in OR. When all groups were compared with the normal weight/lower SES group, the highest OR was for the obese/higher SES group (2.32 95% CI 2.05–2.64 for females and 1.99 95% CI 1.83–2.13 for males). Conclusions: Both BMI and SES are co‐independently associated with asthma in adolescent males and females Abstract : We investigated the associations of BMI and socioeconomic status with asthma prevalence in adolescents. BMI was found to have a J‐curve association in boys and a monotonic association in girls. Socioeconomic status had a monotonic association with asthma in both sexes. BMI and socioeconomic status were independently associated with asthma.